Model for e-government initiative in public sector in Jordan - Al-Naimat, Ali Mohammad Mahmod (2015)
E-government has become a global interest since it extended the public services through information communication technology (ICT) to allow access to information, improve transparency and efficiency. Many governments are interested to implement successful e-government initiatives. However, e-government implementation is not a simple task since the developing countries cannot directly adopt the implementation of e-government model which is mainly built in the context of developed countries. Previous studies have shown that many egovernment projects in developing countries, like Jordan have encountered various problems after implementation phase. Hence, the objective of this study is to develop an e-government initiative model for the public sector in Jordan. In this study, unstructured interviews were conducted as a method for collecting the data. Thirty respondents involved in e-government projects such as managers, general managers and other levels of decision makers were selected from three Jordanian ministries namely the Ministry of Information and Communication Technology, Ministry of Education and Ministry of Labour. The initial success factors for e-government initiatives in Jordan were identified and analyzed qualitatively. Delphi technique was also used to determine and validate the critical success factors (CSFs). Ultimately, a novel Ali, Syazwan & Ruzaini’s e-government initiatives model for has been developed in this research. The model has four stages: (1) Emerging and Information Dissemination; (2) Two-Way Communication; (3) Integration and (4) E-democracy. The findings also revealed seven CSFs that should be taken into account to implement the e-government model which include top management support, vision and strategy, funding, information technology (IT) infrastructure, user computer efficacy, awareness and resistance to change. This study contributes to the body of knowledge in Socio Technical Theory (STT) toward the development of egovernment initiatives model for public sector in Jordan. The empirical data from the study may provide input for government agencies to plan, design and implement future ICT projects in Jordan.